Muscle activity and emotional behavior changes in rats with chronic brain ischemia via comprehensive pathogenetic correction - Kirchev, V. (Journal of Education, Health and Sport, 2023)
Cerebrovascular pathology has evolved from a medical concern to a social issue, with the efficacy of secondary neuroprotection remaining a pertinent question. While some investigations have been conducted to elucidate the effectiveness of a comprehensively grounded pharmacological correction scheme under conditions of experimentaly induced chronic brain ischemia, further refinement is necessary to understand the behavioral effects of animals, dosages, routes of administration of pharmacological agents, and analysis of obtained data. The aim of this study was to assess the effectiveness of applying Semax and hopantenic acid in the comprehensive treatment of motor disorders and established neurological impairments in rats with experimentally induced chronic brain ischemia. We determined that rats with chronic brain ischemia exhibit muscular dysfunctions and experience pronounced disturbances in emotional behavior from the first day. It has been demonstrated that the separate and combined application of Semax and hopantenic acid contributes to the restoration of muscle activity, normalization of coordination, and emotional behavior in rats with chronic brain ischemia. The most significant neuroprotective effect in rats with chronic brain ischemia was observed with the combined administration of Semax and hopantenic acid, starting from the 3rd day of the trial. The subsequent in the series of anti-ischemic effectiveness is the impact of Semax from the 3rd day of the experiment. The least pronounced neuroprotective effect was exhibited by hopantenic acid, starting from the 5th day of the experiment. We consider these findings to be an experimental foundation supporting the feasibility of clinically testing the effects of combined Semax and hopantenic acid administration, capable of restoring functional disorders caused by chronic brain ischemia. In conclusion, the observed effectiveness of the developed pathogenetically justified complex for the correction of post-ischemic muscle dysfunction and disorders indicates the development of an anti-ischemic effect, as well as the fundamental possibility of improving the treatment for patients with chronic brain ischemia through clinical intranasal administration of Semax, either alone or in combination with hopantenic acid. However, for a more comprehensive understanding of the temporal and dose-dependent effects of this complex pathogenetic correction scheme on other disorders and dysfunctions related to chronic brain ischemia and to formulate final conclusions, it is essential to conduct separate series of experimental studies.